The Translation and Commercialisation of Biomarkers for Cardiovascular Disease—A Review - Saleh, Soloman; George, Jacob; Kott, Katharine A.; Meikle, Peter J.; Figtree, Gemma A. (Frontiers in Cardiovascular Medicine, 2022)
As a leading cause of mortality and morbidity worldwide, cardiovascular disease and its diagnosis, quantification, and stratification remain significant health issues. Increasingly, patients present with cardiovascular disease in the absence of known risk factors, suggesting the presence of yet unrecognised pathological processes and disease predispositions. Fortunately, a host of emerging cardiovascular biomarkers have shown great promise in both laboratory settings and clinical trials. These have demonstrated improved predictive value additional to widely accepted biomarkers as well as providing insight into molecular phenotypes beneath the broad umbrella of cardiovascular disease that may allow for further personalised treatment regimens. However, the process of translation into clinical practice – particularly navigating the legal and commercial landscape – poses a number of challenges. Practical and legal barriers to the biomarker translational pipeline must be further considered to develop strategies to bring novel biomarkers into the clinical sphere and apply these advances at the patient bedside.